(Technical and Engineering Design of Granulated cocoa for small scale industry) - Sudibyo, Agus; Sapto Hartanto, Eddy; Yulistia, Aan (Balai Besar Industri Agro, 1998)
Â The cacao production in Indonesia was increased very rapidly in the last five years. However, almost all of the cacao production in Indonesia was exported as cacao bean, meanwhile there were only a few of cacao processing industry top process the cacao bean become chocolate products. These condition was not advantaging for cacao and chocolate industry development, because the added value of cacao bean was small. Therefore, it was needed a strategic development of cacao products. In this case , divesrsification of cacao products for small scale industry was one of the alternative strategic for cacao product development. The study aimed at designing and engineering a set of equipment for small scale industry and material formulation for grain chocolate production. It was concluded that designing and engineering a set of grain chocolate equipment could be implementation for small scale industry by modification. The capacity of cacao granulator ia 4,16 kg per hour. Efficiency of the granulator is 74,8% and the temperature in the cooling tunnel is 10 - 12 C. The grain cocoa product is fullfilled the requirement of Indonesia National Standard (SNI), however the texture and appearance is still have to be improved.